222k views
1 vote
Factor the following expression
10x^5+5x^3-14x^2-7-

Factor the following expression 10x^5+5x^3-14x^2-7--example-1
User Lalli
by
6.3k points

1 Answer

4 votes

Answer:

C. (5x^3-7)(2x^2+1)

Explanation:

Given expression is,

10x^5+5x^3-14x^2-7

=10x^5-14x^2 + 5x^3 - 7 (By the commutative property)

=2x^2(5x^3-7)+5x^3-7 (Taking 2x^3 common from first two terms )

=(5x^3-7)(2x^2+1) (Taking 5x^3-7 common from both terms)

\implies 10x^5+5x^3-14x^2-7=(5x^3-7)(2x^2+1)

Hence, Option C is correct

User Daniel Stenberg
by
5.5k points